PKM Pemberdayaan Masyarakat Dalam Pencegahan Stigma Kusta - Diah Ratnawati; Titiana Siregar; Yuri Nurdiantami (STKIP Andi Matappa, 2022)
Leprosy is an infectious disease that is still synonymous with a curse, giving rise to stigma in society. Community stigma arises because of a lack of understanding of leprosy, leprosy facts, and myths. Therefore, it is crucial to empower the community with a health promotion strategy through health care and self-care training. Prevention of Stigma Leprosy with PKM activities is carried out to provide easy access to information to the community to obtain a correct understanding of leprosy. In addition, self-care training in cadres, families, and lepers is in the form of assessing the level of disability, writing on the defect prevention recording form, and training for sensory and motor enhancement of the eye and extremities to prevent disability. PKM activities significantly affect the knowledge of leprosy, attitudes towards leprosy. Leprosy stigma with a p-value of 0.000 (<0.005). Mean value before and after given PKM program there is a significant difference with the order of increased significance in the negative value of leprosy stigma 13.11 followed score attitude towards good leprosy of 3.58. The value of knowledge of good leprosy is 1.54. Then health workers must do cadre assistance and family in caring for family members, especially lepers, through PKM, increasing knowledge about leprosy, leprosy-related attitudes, leprosy stigma, and independent care for the prevention of disability due to leprosy.